Risk Mitigation Strategies in Implementing Scrum Framework for Internet-Based IT Companies in Indonesia - Rahayu, Flourensia Sapty; Indrawan, Toni; Kamarudin, Shafinah (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2020)
To date many Information Technology Companies in Indonesia implement Scrum Framework which is one of the frameworks that uses Agile principles. The implementation of the Scrum Framework does not guarantee that these companies will be free from risk, since many risks will also appear during the implementation of the framework itself. Therefore, risk management strategies are needed to mitigate these risks. This research is a qualitative research to manage risk due to the implementation of Scrum Framework in software development of IT companies, especially in Indonesia. Interviews have been conducted to the Scrum stakeholders in three IT Companies to gather some initial data to be analyzed further using Qualitative Content Analysis Method and Risk Breakdown Structure. Our finding show that there is 17 Risk Registers and their Mitigation Strategies for the implementation of Scrum Framework in Indonesian IT Companies. Furthermore, it can be used as guidelines for decision making about whether to implement this framework in their core businesses.